Pelaksanaan Pembentukan Kegiatan Ekstrakurikuler Drum Band SMP Negeri 5 Kerinci - Egi Yonil; Erfan Erfan (SENDRATASIK UNP, 2021)
This study aims to identify and describe the implementation of Drum Band extracurricular activity at SMP Negeri 5 Kerinci. This is a qualitative research using descriptive method. The data were collected through literature study, observation, interview, and documentation. The research instrument used was the researcher itself. It was also supported by supporting instruments such as notebooks, stationaries, and a cellphone camera. From the results of the study, it can be described that there are some stages in the implementation of Drum Band Extracurricular activity at SMP Negeri 5 Kerinci. The stages start from selecting members, determining practice materials, determining practice schedules, doing rehearsals, and performing the Drum Band. To get maximum results, the coach creates two forms of training.  One is the routine exercises carried out on Saturdays during self-development lessons, and another is the additional exercises carried out two weeks before participating in the competition. The first exercise begins with a group practice of musical instruments and is continued with a combined practice of all musical instruments.